2008
DOI: 10.1002/mabi.200800005
|View full text |Cite
|
Sign up to set email alerts
|

Development of Electroactive and Elastic Nanofibers that contain Polyaniline and Poly(L‐lactide‐coε‐caprolactone) for the Control of Cell Adhesion

Abstract: In this work, electrically conductive polyaniline (PAni) doped with camphorsulfonic acid (CPSA) is blended with poly(L-lactide-co-epsilon-caprolactone) (PLCL), and then electrospun to prepare uniform nanofibers. The CPSA-PAni/PLCL nanofibers show a smooth fiber structure without coarse lumps or beads and consistent fiber diameters (which range from 100 to 700 nm) even with an increase in the amount of CPSA-PAni (from 0 to 30 wt.-%). However, the elongation at break decreases from 391.54 +/- 9.20% to 207.85 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(107 citation statements)
references
References 44 publications
7
99
1
Order By: Relevance
“…For example, Schwann cells cultured on electrically conductive melanin films accelerated their proliferation, and rat pheochromocytoma PC12 cells enhanced extension of their neurites (Bettinger et al, 2009). Similarly, composite nanofibers made of electrically conductive polyaniline blended with poly(L-lactide-co-epsilon-caprolactone) enhanced the adhesion and proliferation of C2C12 murine skeletal muscle myoblasts, as well as their differentiation towards myotubes (Jeong et al, 2008;Jun et al, 2009). The mechanisms of the positive effects of electroactive materials on cell colonization and function (which can be further enhanced by additional electrical stimulation of cells through the materials) have not yet been fully elucidated and systemized.…”
Section: Nanodiamondmentioning
confidence: 99%
“…For example, Schwann cells cultured on electrically conductive melanin films accelerated their proliferation, and rat pheochromocytoma PC12 cells enhanced extension of their neurites (Bettinger et al, 2009). Similarly, composite nanofibers made of electrically conductive polyaniline blended with poly(L-lactide-co-epsilon-caprolactone) enhanced the adhesion and proliferation of C2C12 murine skeletal muscle myoblasts, as well as their differentiation towards myotubes (Jeong et al, 2008;Jun et al, 2009). The mechanisms of the positive effects of electroactive materials on cell colonization and function (which can be further enhanced by additional electrical stimulation of cells through the materials) have not yet been fully elucidated and systemized.…”
Section: Nanodiamondmentioning
confidence: 99%
“…Li et al (2006) also showed that the incorporation of PANI into gelatin solution decreased the fibre diameter from 803 ± 121 nm for pure gelatin fibres to 61 ± 13 nm for 60:40 PANI-gelatin blend fibres. In yet another study, Jeong et al (2008) showed that by increasing the volume ratios of PANI in poly(L-lactide-co-ε-caprolactone) (PLCL) solution, the diameters of resultant nanofibres decreased from 430 ± 116 nm for pure PLCL to 382 ± 102 nm for PANI/PLCL nanofibres. Table 2 shows the different conductive nanofibrous scaffolds that have been fabricated for various tissue-engineering applications.…”
Section: Electrospun Conductive Polymers For Nerve Tissue Engineeringmentioning
confidence: 99%
“…These researchers also fabricated a conductive biodegradable composite material made of PPy nanoparticles and poly(D,L-lactide), applied electrical stimulation after seeding fibroblasts on them and found similar upregulations (Shi et al, 2004). Jeong et al (2008) fabricated nanofibrous scaffolds containing PANI and poly(L-lactideco-ε-caprolactone) and investigated the behaviour of human dermal fibroblasts, NIH-3T3 fibroblasts and C2C12 myoblasts on this scaffold. The growth of NIH-3T3 fibroblasts was enhanced by stimulation of various DC flows.…”
Section: Application Of Electrical Stimulation In Nerve Tissue Enginementioning
confidence: 99%
See 1 more Smart Citation
“…However, the preparation of such nanoconstructs has been essentially restricted to the combination of biodegradable polymer with small electroactive oligomers (e.g. oligothiophenes [26] and oligoanilines [27,28], polyaniline (PAni) or PPy derivatives [20,[29][30][31]. On the other hand, antecedents on drug delivery systems fabricated with nanofibers based on biodegradable polymers-CP blends are very scarce.…”
Section: Introductionmentioning
confidence: 99%